2018
DOI: 10.1371/journal.pone.0204254
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy may worsen the survival rate in rats with monocrotaline-induced pulmonary arterial hypertension

Abstract: Although oxygen therapy rapidly improves arterial oxygen saturation in idiopathic pulmonary arterial hypertension, the effects of chronic administration of oxygen are unknown. The purpose of the present study was to investigate the effects of chronic oxygen therapy on the histological changes and survival rate in rats with idiopathic pulmonary arterial hypertension. Idiopathic pulmonary arterial hypertension was induced by monocrotaline injection. The rats were then randomly assigned to receive or not receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Rats that received MCT and oxygen therapy recruited leukocytes that promoted RV inflammation and failure. And despite increases in SOD activity, antioxidants were not able to sufficiently counteract the oxidative stress caused by the combination of MCT and chronic oxygen therapy (Fujita et al, 2018).…”
Section: Past Failures Of Antioxidant Ph Therapies In the Rv And Lungsmentioning
confidence: 99%
“…Rats that received MCT and oxygen therapy recruited leukocytes that promoted RV inflammation and failure. And despite increases in SOD activity, antioxidants were not able to sufficiently counteract the oxidative stress caused by the combination of MCT and chronic oxygen therapy (Fujita et al, 2018).…”
Section: Past Failures Of Antioxidant Ph Therapies In the Rv And Lungsmentioning
confidence: 99%
“…Our results also confirmed that administration of MCT induced heart failure, increased HIF-1 alpha (a marker of hypoxia), increased lactate, and enhanced the glycolytic system. Recent reports showed that excessive utilization of mitochondrial metabolism in the pathogenesis of heart failure induces higher than normal oxidative stress (ROS) and apoptosis 5 ) . Furthermore, normalized oxygen administration for acute heart failure can increase myocardial necrosis 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, oxygen administration for heart failure has recently been reported to cause myocardial damage. Fujita et al reported that overexploitation of fatty acid metabolism during heart failure causes more oxidative stress (reactive oxygen species [ROS]) in mitochondria than usual, leading to myocardial injury 5 ) . Glucose loading, which increases glucose metabolism in heart failure, may suppress fatty acid metabolism in mitochondria and exert a protective effect on the myocardium.Therefore, in this study we generated rat models of heart failure to examine the effects of forced turnover of glycolytic metabolism on the myocardium and physical functions.…”
Section: Introductionmentioning
confidence: 99%
“…During the day, NHF20 increased mean SpO 2 from approximately 91 to 93%, while at nighttime, where hypoxia has previously been described to be more severe [ 8 , 10 ], mean oxygen saturation was approximately 88% in the same patients. Faster and greater increases in oxygen saturation have been shown to be associated with increased levels of oxygen radicals, which in turn are associated with poor functional status in patients with heart failure [ 43 , 45 47 ]. It appears that differences in the effects of NHF20 on oxygen saturation also account for the unwanted increase in sympathetic drive during daytime and a beneficial reduction in sympathetic drive at night in the present study.…”
Section: Discussionmentioning
confidence: 99%